Violent Acts and Violent Times: A Comparative Approach to Postwar Homicide Rates - Archer, Dane; Gartner, Rosemary (American Sociological Review, 1976)
The idea that waging war might increase the level of domestic violence in warring societies has occurred to many researchers. Discussions of this possibility have been limited to a very small number of case studies–often as limited as the experience of a single nation in a single war. A major obstacle to the general investigation of this question has been the unavailability of comparative data on homicide rates. Over a three-year period, a Comparative Crime Data File was assembled. The file includes time-series rates of homicide for roughly 110 nations beginning in about 1900. Postwar rather than wartime homicide rates were analyzed, since postwar data appear much less problematic and are likely to be affected by artifacts in only a conservative direction. The homicide data were analyzed to: (1) determine if postwar increases did occur and (2) identify which of seven competing theoretical models appeared to offer the most adequate explanation. The homicide rate changes after 50 were compared with the changes experienced by 30 control nations. The major finding of the study was that most of the nation-wars in the study did experience substantial postwar increases in their rates of homicide. These increases were pervasive, and occurred after large wars and smaller wars, with several types of homicide rate indicators, in victorious as well as defeated nations, in nations with both improved and worsened postwar economies, among both men and women offenders and among offenders of several age groups. Homicide rate increases occurred with particular consistency among nations with large numbers of combat deaths. Using homicide and other data, it was possible to disconfirm or demonstrate the insufficiency of six of the seven explanatory models. (Abstract Adapted from Source: American Sociological Review, 1976. Copyright © 1976 by the American Sociological Association) War Effects Homicide Rates Homicide Risk Factors Homicide Causes Homicide Trends and Patterns Homicide Incidence and Prevalence Violence Causes Violence Rates Violence Risk Factors Adult Violence 07-02